The validation of estrogen receptor 1 mRNA expression as a predictor of outcome in patients with metastatic non-small cell lung cancer - Atmaca, Akin; Al‐Batran, Salah-Eddin; Wirtz, Ralph Markus; Werner, Dominique; Zirlik, Sabine; Wiest, Gunther; Eschbach, Corinna; Claas, Silke; Hartmann, Arndt; Ficker, Joachim Hans; Jäger, Elke; Brueckl, Wolfgang Michael (International journal of cancer, 2014)
The prognostic role of estrogen receptors in lung cancer is not validated. Results from patients with early stage non-small lung cancer patients indicate a prognostic role of estrogen receptor 1 (ESR1) mRNA expression in these patients. Automated RNA extraction from paraffin and RT-quantitative PCR was used for evaluation of tumoral ESR1 and progesterone receptor (PGR) mRNA expression. The test cohort consisted of 31 patients with advanced or metastatic non-small cell lung cancer (NSCLC) patients, treated in a first-line registry trial. For validation, 53 patients from a randomized multicentre first-line study with eligible tumor samples were evaluated. There was no significant correlation of ESR1 expression with clinical characteristics. ESR1 high expression was of significant positive prognostic value in the training set with a median overall survival (OS) of 15.9 versus 6.2 months for high versus low ESR1 expression patients (p = 0.0498, HR 0.39). This could be confirmed in the validation cohort with a median OS of 10.9 versus 5.0 months in ESR1 high versus low patients, respectively (p = 0.0321, HR 0.51). In the multivariate analysis adjusted for histological subtype, gender, age and performance status, ESR1 expression remained an independent prognostic parameter for survival in both cohorts. In contrast to ESR1, PGR expression was not able to separate prognostic groups or to predict outcome significantly (for OS; p = 0.94). Our study shows that ESR1 mRNA as assessed by qPCR represents a reliable method for detecting ESR1 expression in NSCLC and that ESR1 expression is an independent prognostic factor in metastatic NSCLC.
Gesehen am 18.08.2020
First published: 31 Oct 2013